Peran Guru Bimbingan Konseling dalam Meningkatkan Kedisiplinan Tata Tertib Sekolah Siswa Kelas X SMKN 1 Cilimus Kuningan - Reza Nurul Ardhiansyah (Journal of Current Research in Management, Policy, and Social Studies, 2024)
This study aims to describe the role of Guidance and Counseling (GC) teachers in improving school discipline among tenth-grade students at SMKN 1 Cilimus, Kuningan. Using a descriptive qualitative approach, data were collected through direct observation, in-depth interviews, and documentation. The findings reveal that student discipline remains low and is largely reactive motivated by sanctions rather than intrinsic awareness. GC teachers play a strategic role as informants, counselors, facilitators, and home visit coordinators. Sanctions are applied in a structured and educational manner, not merely as punishment, but to foster understanding of consequences. Additionally, humanistic and religious approaches, such as the